Plant regeneration of Michelia champaca L., through somatic embryogenesis - Armiyanti; Abdul Kadir, Mihdzar; Kadzimin, Saleh; Panjaitan, Syaiful Bahri (Academic Journals, 2010)
Michelia champaca L. is a woody ornamental tree species which has high commercial value to be used as a basic material for perfume, cosmetic, and medicine. The development of an efficient plant regeneration system for M. champaca is essential for the production of Champaca planting material and precondition for genetic manipulation. Plant regeneration systems of M. champacathrough somatic embryogenesis derived from immature seed of M. champaca L. which was successfully developed in this study. MS medium supplemented with 2 mgL-1, NAA produced highest percentage of embryogenic callus formation of (43%). The embryogenic cells proliferated and formed somatic embryos (30%) after four to six months of culture in the same medium. Meanwhile, on germination of somatic embryos, hormone free of MS medium resulted in highest percentage of normal plantlets produced (45%) compared with other germination medium which is containing different GA3 concentrations with ranges from 1 - 8% somatic embryos germinated.